EIMERIOSIS EN CRÍAS DE ALPACAS: ESTUDIO ANÁTOMO HISTOPATOLÓGICO - Palacios E., César (2013)
The death associated with diarrhea of 7 newborn alpacas from the Maranganí-Cuzco community was studied. The animals showed signs of reddish watery diarrhea, dehydration, anorexia, and weakness. The gross lesions in the small intestine mucosa were reddish, augmented and necrotic, with severe hiperemia and gas. They showed small white foci of 0.2 cm diameter located at the final part of yeyuno and ileon. Two types of oocysts were detected. The first was piriform-shape of 90 microns (Eimeria macusaniensis) and the second, elipsoidal-shape of 30 microns (Emeria lamae). Microscopic lesions presented an acute, diffuse, and severe catarrhal necrotic enteritis with hiperplasia of Lieberkun cripts, and thickness or shortness of the villi, with moderate to severe corionic infiltration of eosinophils, linfocites and plasmacites, along with numerous endogenous forms: schizonts, microgamonts, macrogamonts, and nonsporulated oocysts at level of the crypts and villi.